G147(P) Evaluating the Impact of Introducing Advanced Paediatric Life Support Training in a Teaching Hospital in Zambia. (4th June 2013) - Tyndall, P; Seddon, E; Somwe, S Wa; Seddon, P
Abstract : Aims: The effective treatment of acutely sick children in resource-poor settings (including teaching hospitals in most developing countries) is limited by resources, but also by knowledge, skills and attitudes. Introducing rigorously-assessed, multidisciplinary training in paediatric life support may help address these issues, but there is limited evidence of the effectiveness of this approach. As part of a Zambia-UK Health Link, we carried out a needs assessment at the Zambian partner's paediatric unit, which demonstrated that (a) most deaths were occurring within 48 hours of admission, and (b) staff expressed lack of confidence in dealing with acutely sick children. After assessing the options, we collaborated to establish Advanced Paediatric Life Support (APLS) training in Zambia. Methods: We assessed the impact of the APLS programme in 3 ways: (a) by semi-structured interviews with trainees, to assess the perceived relevance and impact of the training, with a mixture of free-form and 5-point Likert responses (b) by comparing mortality figures, from hospital records, before and after APLS training commenced in 2011 (c) by examining changes in clinical practise from a sample of case records (vital signs/emergency treatment recorded), after APLS training commenced. Results: In answer to "How relevant was the course to your everyday practise?", median response was 5 "Very relevant" – range 3–5; for "Will doing this course change how you practise?", median (range) response was 5 "A lot" (3–5). Total mortality following admission decreased from 691 (15% of admissions) during Oct-Dec 2010 to 530 (12%) during Oct-Dec 2011 (p < 0.001). Deaths on the day of admission also decreased, from 149 (3.2%) to 102 (2.3%) respectively (p < 0.01). The proportion of patients with vital signs and initial management recorded showed a trend to increase from 2010 to 2011, though this was only significant for recording of heart rate. Conclusion: APLS training is perceived as relevant to their needs by healthcare staff in a Zambian tertiary paediatric unit, and has been associated with evidence of improved management and reduced in-hospital mortality. Further work is needed to establish whether the improvements were due to the training, and whether they are sustainable.